MOG1 restores the expression and function of SCN5A-p.R104W through sec23a-mediated forward trafficking. (25th November 2020) - Luo, L; Wang, Y; Du, Y; Dong, C; Ma, A; Wang, T
Abstract: Background: Brugada syndrome (BrS) is an inherited disease which causes fatal arrhythmias and sudden cardiac death. Mutations in SCN5A gene, which encoding cardiac sodium channel (NaV1.5), are the most common genotype of BrS patients. Some SCN5A-related variants were reported to retain NaV1.5 in endoplasmic reticulum (ER) due to trafficking deficiency. MOG1 was previously reported to interact with NaV1.5 and increased sodium current (INa) through enhancing the trafficking. However, its molecular mechanisms are still unclear. Coat protein complex II (COPII) is responsible for the ER to Golgi transport. Sec23 forms the inner coat of COPII and participates in cargo proteins selection. Purpose: To demonstrate that MOG1 rescues SCN5A-related variants by enhancing the forward trafficking through Sec23a-NaV1.5 interaction. Methods: Site directed mutagenesis, immunofluorescence staining, biotinylation assay, Western blot analysis and whole-cell patch clamp recording were used. CRISPR/Cas9 was used to knock out Sec23a expression in HEK293 cells. Results: We found that SCN5A-p.R104W was characterized as reduced NaV1.5 level and lack of INa. The variant SCN5A-p.R104W was mainly distributed in ER. MOG1 could rescue the total and surface expression of SCN5A-p.R104W but could not restore INa (Figure 1a). Considering that most patients are heterozygous, co-transfection of SCN5A-WT and SCN5A-p.R104W were obtained. We found MOG1 could increase both NaV1.5 level and INa of heterozygous expressed SCN5A-p.R104W. We further revealed an interaction between NaV1.5 and Sec23a by co-immunoprecipitation (Co-IP) assay. The interaction between NaV1.5 and Sec23a was increased by MOG1, which indicates that Sec23a participates in MOG1-mediated increase in NaV1.5 level (Figure 1b). Knockout of Sec23a reduced cell surface, but not total, NaV1.5 level (Figure 1c and 1d). Next, the Sec23a knockout HEK293 cells were co-transfected with SCN5A-p.R104W and pcDNA3 or MOG1. MOG1 could not increase SCN5A-p.R104W protein level in Sec23a knockout cells. Conclusion: Our data demonstrated a novel mechanism that MOG1 restores the expression and function of SCN5A-p.R104W by enhancing its forward trafficking through Sec23a-NaV1.5 interaction. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Natural Science Foundation of China